2016
DOI: 10.1186/s13071-016-1925-3
|View full text |Cite
|
Sign up to set email alerts
|

First report on human-biting Culex pipiens in Sweden

Abstract: Culex mosquitoes are vectors of several bird-hosted arboviruses that cause outbreaks in Europe, such as Sindbis virus and West Nile virus. Recently, the human-biting form of Culex pipiens, Cx. pipiens biotype molestus, was found causing big nuisance in a housing cooperative in Gothenburg in southern Sweden, confirmed by molecular identification. This is the first report of human-biting Culex in Scandinavia, signalling increased risk of arbovirus infection in northern Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Recent and historical references have been made to Cx. pipiens biotype molestus being present in Finland, and in northern Europe as a whole (Utrio, ; Hesson et al ., ; Lindström, ); however, this biotype was not considered within the scope of this study. Although there is a possibility that the species inhabits Åland, the molecular work for this species will be conducted in another study will examine Cx.…”
Section: Discussionmentioning
confidence: 99%
“…Recent and historical references have been made to Cx. pipiens biotype molestus being present in Finland, and in northern Europe as a whole (Utrio, ; Hesson et al ., ; Lindström, ); however, this biotype was not considered within the scope of this study. Although there is a possibility that the species inhabits Åland, the molecular work for this species will be conducted in another study will examine Cx.…”
Section: Discussionmentioning
confidence: 99%
“…Cx. pipiens f molestus has been found previously in Gothenburg (Hesson, Schäfer et al 2016) and has been reported from Stockholm in 1934, reviewed in (Lindström 2017). There are also findings of three Cx.…”
Section: Introductionmentioning
confidence: 79%
“…Our study analyzed specimens sent in by people experiencing mosquito nuisance in the south of Sweden and compared with several collections of Culex mosquitoes collected in traps in rural areas in the south of Sweden. Most of the Cx pipiens f molestus specimens were collected in Gothenburg where the bioform has been recently described (Hesson, Schäfer et al 2016). This makes it hard to evaluate the true distribution of the molestus bioform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pipiens pipiens that mainly feeds on birds and Cx. pipiens molestus that feeds on mammals including humans (Farajollahi et al 2011, Hesson et al 2016, Lindström 2017).…”
Section: Discussionmentioning
confidence: 99%